Politics and Mass Communication: Rethinking the Interplay of Global Media and Democracy in Post Arab-Spring Morocco - Ferrati, Abdesselam (European Scientific Journal, ESJ, 2021)
Global media have usually been regarded as a fundamental guarantee of democracy. They are not mere superficial communication outlets; they are rather crucial agents of change on which the progress, prosperity, and stability of societies depend. This article addresses this relationship and analyzes the impacts of the rapid and unruly digitized invasion on participatory citizenship in Morocco. It explores why democracy, freedom, and change have become inescapable consequences of the proliferation of digitized communication tools and the uncensored access to modern media technologies, auspicating the demise of the nation-state in favor of direct democracy (Katz, 2009; Potter, 2021; Turner, 2016). The conservation of cultural pluralism and the boosting of cultural awareness ultimately depend on how we handle media outlets and how we adapt international information and the massive dissemination of digital products. This research argues that the profuseness of new media technologies permits new digital coalitions and solidarities across spatial, racial, and cultural boundaries and resources for producing new meanings and new identities in Morocco. Furthermore, this study sought to answer among other issues the extent to which local cultural processes are intemperately threatened, shaped, and amplified by globalizing influences and a massive flow of contentious and bigotry-instigating ideas.